Prevalence and histopathology of Sarcocystosis in slaughtered carcasses in southeast Iran - Shahraki, Mahdi Khoshsima; Ghanbarzehi, Abdolhakim; Dabirzadeh, Mansour (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Sarcocystis spp. are common parasites and in terms of economics and pathogenicity in domestic animals is important. The purpose of this work was to define the rate of contamination of slaughtered carcasses of cattle to Sarcocystis using digestive and histopathological methods in southeast Iran. Materials and Methods: In this descriptive laboratory study for 1 year, 500 carcasses were examined and isolated bradyzoites of Sarcocystis with the digest method. Also, tissue samples from the esophagus and diaphragm were considered for pathologic studies and stained with hematoxylin and eosin of sections of histopathological. Results: The results showed that the highest contaminations were in imported male animals aged 2–3 years old in the spring. There was a significant difference (p < 0.05) in the prevalence rate with the sex and race of cattle but no significant difference (p > 0.05) in the prevalence rate with age and season. Conclusion: Infection with Sarcocystis is common in oxen in this region. The imported cattle are more infected. It seems that racing and the environmental condition affect the prevalence of Sarcocystosis. http://doi.org/10.5455/javar.2018.e288